The Online Citizens Project: Effects oftransitional peer support groups facilitated by peer support workers for persons living with severe mental illness in times of the Covid-19 pandemic - Pelletier, Jean-François; Houle, Janie; Goulet, Marie-Hélène; Giguère, Charles-Édouard; Morin, Charles-Albert; Juster, Robert-Paul; Hénault, Isabelle; Denis, Frédéric (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
From August to November 2020, the Online Citizens Project has been offered as a transitional peer support group to persons living with Serious Mental Illness (SMI) in the province of Quebec, Canada. The Citizens’ Project is a support group where participants share their challenges and accomplishments with each other and receive honest and confidential feedback. These groups had a personal-civic recovery focus and consisted of a series of 10 weekly 90-minute online workshops. To evaluate the impact of the intervention on the participants’ sense of citizenship, all study participants completed the 23-item French version of the Citizenship Measure before (T1) and after (T2) the intervention (?14 weeks between T1 and T2). The mean and standard deviation differences between the two measurement times were compared between the experimental group and the control group. The mean score to the Citizenship Measure for the experimental group varied by -0.4%. The mean score for the experimental group varied by -5.5%. For the control group, there was a decrease in the means for each of the 5 sub-scales of the Citizenship Measure. In total, the difference was statistically significant (P=.04). Results suggest that the Online Citizens Project had a protective effect on the sense of citizenship of the participants living with SMI in the experimental group compared to those in the control group. The Citizenship Measure can be used to gauge the effects of such an online intervention, intentionally designed to promote the exercise of citizenship, namely the Citizens Project.